EVALUASI KONDISI LINGKUNGAN DAN SARANA PENYELAMATAN PADA GEDUNG PERKULIAHAN TERHADAP BAHAYA KEBAKARAN - Fadillawaty Saleh; Sinta Rizky Amalia; Hakas Prayuda; Lilis Tiyani; Bella Lutfiani Al Zakina (Jurusan Teknik Sipil, Fakultas Teknik Sipil dan Perencanaan, Universitas Islam Indonesia, 2021)
Many aspects must be considered in the building's design so that the construction is sturdy and can be used according to its function. An important aspect that is often overlooked is the aspect of fire safety. This study aims to evaluate environmental conditions and safety facilities in buildings against fire hazards. The buildings reviewed are the Postgraduate Building, E6, E7, and F3 of the Muhammadiyah University of Yogyakarta. The research method used in this research is a qualitative approach, and the primary data is obtained by direct observation in the field and interviews with the person in charge of the building. This study indicates that the environmental conditions of the postgraduate building, E6, E7, and F3, are not in good condition because each building gets a condition value of 51.67%; 50.56%; 52.22%; and 50%. The rescue facilities in the postgraduate building, E6, and E7 are good; although there are some shortcomings, the value of the condition of each building is 85.98%, 87.41%, and 87.41%. The rescue facility in the F3 building is quite good, with a condition value of 65.81%.